Spread of Sheep Gastrointestinal Stranglyatos in Bukhara Region - o‘g‘li, Ulukov Behzod Karamat; Abdumajidovich, Jabbarov Shuxrat (American Journal of Biology and Natural Sciences, 2025)
This article presents data on the level of helminthiasis infection of sheep and the distribution of the main helminthiasis in various districts of the Bukhara region, which is considered the southwestern region of our republic, this year.